UCITA a disaster in progress. - Kaner, C. (IEEE spectrum)
Software companies are pushing draconian legislation that would abolish century-old doctrines protecting the rights of users of intellectual property. The author argues that by treating a transaction for software as a license rather than a sale, the Uniform Computer Information Transactions Act would cost us all dearly. UCITA makes enforceable almost any term that the vendor puts into a license contract.